Myocardial strain assessment using cardiovascular magnetic resonance imaging in recipients of implantable cardioverter defibrillators - Tan, Nigel S.; Deva, Djeven P.; Connelly, Kim A.; Angaran, Paul; Mangat, Iqwal; Jimenez-Juan, Laura; Ng, Ming-Yen; Ahmad, Kamran; Kotha, Vamshi K.; Lima, Joao A. C.; Crean, Andrew M.; Dorian, Paul; et al. (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Cardiovascular magnetic resonance (CMR) is increasingly used in the evaluation of patients who are potential candidates for implantable cardioverter-defibrillator (ICD) therapy to assess left ventricular (LV) ejection fraction (LVEF), myocardial fibrosis, and etiology of cardiomyopathy. It is unclear whether CMR-derived strain measurements are predictive of appropriate shocks and death among patients who receive an ICD. We evaluated the prognostic value of LV strain parameters on feature-tracking (FT) CMR in patients who underwent subsequent ICD implant for primary or secondary prevention of sudden cardiac death. Methods Consecutive patients from 2 Canadian tertiary care hospitals who underwent ICD implant and had a pre-implant CMR scan were included. Using FT-CMR, a single, blinded, reader measured LV global longitudinal (GLS), circumferential (GCS), and radial (GRS) strain. Cox proportional hazards regression was performed to assess the associations between strain measurements and the primary composite endpoint of all-cause death or appropriate ICD shock that was independently ascertained. Results Of 364 patients (mean 61 years, mean LVEF 32%), 64(17.6%) died and 118(32.4%) reached the primary endpoint over a median follow-up of 62 months. Univariate analyses showed significant associations between GLS, GCS, and GRS and appropriate ICD shocks or death (all p < 0.01). In multivariable Cox models incorporating LVEF, GLS remained an independent predictor of both the primary endpoint (HR 1.05 per 1% higher GLS, 95% CI 1.01–1.09, p = 0.010) and death alone (HR 1.06 per 1% higher GLS, 95% CI 1.02–1.11, p = 0.003). There was no significant interaction between GLS and indication for ICD implant, presence of ischemic heart disease or late gadolinium enhancement (all p > 0.30). Conclusions GLS by FT-CMR is an independent predictor of appropriate shocks or mortality in ICD patients, beyond conventional prognosticators including LVEF. Further study is needed to elucidate the role of LV strain analysis to refine risk stratification in routine assessment of ICD treatment benefit.